City marketing: online communication plan for the city of Lisbon - Altrichter, Benjamin (2013)
City Marketing represents marketing efforts of cities in order to attract more visitors. Today, we are confronted everyday with marketing campaigns in all different communication media promoting countries, cities or events. Cities are competing for visitors on a global scale, forcing them to adapt successful marketing strategies for gaining and retaining costumers. Yet, City Marketing still remains an unknown chapter for a big part of the general public and even for some decision makers in city administration. Bad practices in the past and the improper use of municipal funds originated a negative image of City Marketing and the nonacceptance of this marketing practice by marketers. However, City Marketing is a powerful tool to successfully raise a cities’ competitive position and the number of visitors. This project focuses on online marketing strategies of cities. The Internet changed the way how people buy products and how they consume them. The tourism industry is no exception, being one of the most dynamic sectors of the global economy and heavily influenced by online purchase and e-commerce. For the matter of this project, current practices of online marketing and communication will be benchmarked, followed by the creation of an online communication plan for the city of Lisbon.